2021
DOI: 10.3889/oamjms.2021.6102
|View full text |Cite
|
Sign up to set email alerts
|

Can Estrogen Receptor, Progesterone Receptor, and Proliferative Index be Considered as Isolated Prognostic Factors of Overall Survival in Early luminal Breast Cancer?

Abstract: BACKGROUND: There are a number of proven molecular and pathological markers important for the prognosis for OS of early luminal type breast cancer, but there are still some deficiencies mainly due to the non-linear relationship between the markers and the outcome of the disease. METHODS AND PATIENTS: In this retro-prospective study, clinical and pathological data were provided from 336 patients with breast cancer who underwent breast surgery and treatment between January 2010 and December 2013, and followed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 37 publications
(51 reference statements)
1
2
0
Order By: Relevance
“…Similarly to DFS, there was no significant difference between OS and Ki67 with mean OS in breast cancer patients of luminal subtype B with Ki67 being in the range of 20-40%, was 39.90 months and in Ki67 >40% was 39.42% month. Similar findings were obtained by Karakolevska- Ilova et al in 2021 which could not prove Ki-67 as a prognostic factor for survival in breast cancer of luminal subtype B (Karakolevska-Ilova et al, 2021). This is different from a study by Kim et al in 2013 which stated that Ki-67 expression is related to important prognostic factors both in terms of RFS and OS in luminal type breast cancer patients, but in this study, Ki-67 assessments were distinguished into negative and positive, not distinguished from levels so it was concluded that the presence of Ki-67 factors in breast cancer greatly influenced the development of the disease, but the difference in levels above 20% did not have significant influence (Kim et al, 2013).…”
Section: Analysis Of the Relationship Of Ki67 Expression With Breast ...supporting
confidence: 85%
See 2 more Smart Citations
“…Similarly to DFS, there was no significant difference between OS and Ki67 with mean OS in breast cancer patients of luminal subtype B with Ki67 being in the range of 20-40%, was 39.90 months and in Ki67 >40% was 39.42% month. Similar findings were obtained by Karakolevska- Ilova et al in 2021 which could not prove Ki-67 as a prognostic factor for survival in breast cancer of luminal subtype B (Karakolevska-Ilova et al, 2021). This is different from a study by Kim et al in 2013 which stated that Ki-67 expression is related to important prognostic factors both in terms of RFS and OS in luminal type breast cancer patients, but in this study, Ki-67 assessments were distinguished into negative and positive, not distinguished from levels so it was concluded that the presence of Ki-67 factors in breast cancer greatly influenced the development of the disease, but the difference in levels above 20% did not have significant influence (Kim et al, 2013).…”
Section: Analysis Of the Relationship Of Ki67 Expression With Breast ...supporting
confidence: 85%
“…This is in accordance with the findings of Karakolevska-Ilova et al in 2021 which stated that estrogen receptor expression did not show prognostic significance for OS in breast cancer subtype luminal B. In the study, it was found that the OS of patients with ER expression >10% after 70 months decreased gradually while all patients without or low ER expression lasted longer (more than 100 months) so it can be concluded that ER is not an independent factor that determines the prognosis of the patient luminal subtype B breast cancer (Karakolevska-Ilova et al, 2021).…”
Section: Analysis Of the Relationship Between Er Expression And Breas...mentioning
confidence: 82%
See 1 more Smart Citation